A Multistate Investigation of Antibiotic‐Resistant Salmonella enterica Serotype I 4, [5], 12:i:‐ Infections as Part of an International Outbreak Associated with Frozen Feeder Rodents. (21st May 2015) - Cartwright, E. J.; Nguyen, T.; Melluso, C.; Ayers, T.; Lane, C.; Hodges, A.; Li, X.; Quammen, J.; Yendell, S. J.; Adams, J.; Mitchell, J.; Rickert, R.; et al.
Summary: While most human Salmonella infections result from exposure to contaminated foods, an estimated 11% of all Salmonella infections are attributed to animal exposures, including both direct animal handling and indirect exposures such as cleaning cages and handling contaminated pet food. This report describes the epidemiologic, environmental and laboratory investigations conducted in the United States as part of the response to an international outbreak of tetracycline‐resistant Salmonella enterica serotype I 4, [5], 12:i:‐ infections with over 500 illnesses occurring from 2008 to 2010. This investigation found that illness due to the outbreak strain was significantly associated with exposure to pet reptiles and frozen feeder rodents used as food for pet reptiles. Salmonella isolates indistinguishable from the outbreak strain were isolated from a frozen feeder mice‐fed reptile owned by a case patient, as well as from frozen feeder mice and environmental samples collected from a rodent producing facility (Company A). An international voluntary recall of all Company A produced frozen feeder animals sold between May 2009 and July 2010 occurred. Only 13% of cases in our investigation were aware of the association between Salmonella infection and mice or rats. Consumers, the pet industry, healthcare providers and veterinarians need to be aware of the potential health risk posed by feeder rodents, whether live or frozen. Frozen feeder rodent producers, suppliers and distributors should follow the animal food labelling requirements as described in 21 CFR §501.5, and all packages of frozen feeder rodents should include safe handling instructions. Persons should wash their hands thoroughly with soap and water after handling live or frozen feeder rodents, as well as reptiles or anything in the area where the animals live. Continued opportunities exist for public health officials, the pet industry, veterinarians and consumers to work together to prevent salmonellosis associated with pet food, pets and other animals.